160 Arrhythmia and Heart Failure Substrates in the Right Ventricular Outflow Tract of Adults with Surgically Repaired Tetralogy of Fallot. (31st May 2014) - Schneider, Heiko; Monfredi, Oliver; Murfitt, Lucy; Benett, Hayley J; Temple, Ian P; Knight, David; O'Cualain, Ronan; Dobrzynski, Halina; Hart, George; Kitmitto, Ashraf; Hoschtitzky, Andreas J; Boyett, Mark R; et al.
Abstract : Introduction: Adults with Tetralogy of Fallot (ToF) have an increased risk of heart failure, arrhythmias and sudden death. We sought to investigate whether myocardial remodelling of the right ventricular outflow tract (RVOT) could be responsible. Methods: We collected RVOT myocardial biopsies from 10 ToF patients (6 male) at the time of pulmonary valve replacement. As controls, biopsies from 9 patients (4 male) with left ventricular outflow tract obstruction without evidence of arrhythmia or right-sided heart disease on clinical examination, ECG and echocardiography were collected. We performed: (i) picrosirius red to quantify extracellular matrix (ECM); (ii) qPCR to quantify mRNA for ion channels, transporters, connexins, inflammatory markers and constituents of the ECM; (iii) proteomics (Liquid Chromatography and Mass Spectrometry, MS; on 6 patients per group) to quantify 2000 proteins; and (iii) Western Blot to quantify selected proteins. Results: Mean age during surgery was 32 ± 4 and 22 ± 2 years in the ToF and control groups, respectively. There was no significant difference in the amount of fibrosis on histological analysis. In the ToF patients, there were significant changes in the relative abundance of 19 mRNAs for ion channels, adrenergic receptors, ECM, and two heart failure markers (ANP and BNP). MS highlighted over 300 significant changes between ToF and control patients. A selection of changes identified on qPCR and MS are displayed in Table 1 . Conclusions: The RVOT undergoes significant remodelling in ToF. Changes in ion channels and transporters in ToF patients might alter ionic currents. Risk of arrhythmia may be increased by changes to Ca 2+ -handling and gap junction protein, Cx43. Changes are similar to those described in heart failure and are possibly contributing to the high arrhythmia burden seen in TOF.